Oleander - Zerbst, Fiona (Athlone, South Africa : Modjaji Books, 2009)
Oleander explores life's complexities, both beautiful and poisonous-love, death, art, the aftermath of war and genocide, travel, religion, revelation. More wide-ranging than Zerbst's previous volumes, Oleander charts experiences through which the self may be transformed.
Front Cover; Title Page; Copyright Page; Contents; Remembering S-21, Cambodia; Moths; Relics; Learning to box; Impermanence; Comfort; Red plum blossoms; Hart Crane, 1899-1932; Shepherdess; Death of a dog; Beach-town revisited; July; Possibilities; Volcanic; Politics; The dying fish; Crime fiction; Butterflies; North star; Reading Thom Gunn; Wings; The Temptation of St Anthony; Leaving the summer-house; Beyond; Laguna Frias, Patagonia; Touch; On a lake in Patagonia; Legacy -- after Frida Kahlo; In praise of loss; Fasting; Burials; Shredding; Patterns; In Saigon; Light; Beside the Nile
Print version record.
eBooks on EBSCOhost
Keywords: South African poetry (English); Poésie sud-africaine (anglaise); Poetry by individual poets; FICTION -- General; South African poetry (English); poetry; Poetry; Poetry; Poésie.